Capsule endoscopy in patients with suspected Crohn's disease – is the PillCam worth the swallow?. (13th March 2011) - Kalla, R; McAlindon, M E; Drew, K; Sidhu, R
Abstract : Introduction: Capsule endoscopy (CE) has developed an important role in the investigation pathway of patients with suspected Crohn's disease. However there is paucity of data on the long term outcome in this cohort. We investigated the utility of CE in patients with suspected Crohn's disease and impact on subsequent management. Methods: All patients with suspected Crohn's disease referred routinely for CE between 2003 and 2009 were identified. Data was collected for patient demographics, previous investigations, findings at CE and subsequent follow up. Results: A total of 265 patients were identified, 68% females, mean age 41 years (range 17–82 years). The majority of patients had symptoms of diarrhoea (80%) and abdominal pain (83%), while 33% (n=86) had weight loss. Raised inflammatory markers were present in 65% (n=172) and 18% (n=47) were iron deficient. Nine per cent (n=25) of patients were on non-steroidal anti-inflammatory drugs (NSAID). 94% of patients had colonoscopy prior to CE with TI biopsies in 60% (n=159). Although 20% (n=31/159) were macroscopically abnormal, 18 patients had normal TI histology with 13 showing non specific changes. Small bowel radiology was performed in 90% (n=239) prior to CE where 87% (n=207) were normal and 13% showed non-specific small bowel changes. CE was suggestive of Crohn's disease with the presence of ulcers (>3), oedema, petechiae and erythema in 17% (n=45). On logistic regression, abdominal pain (p=0.01), diarrhoea (p=0.002) and hypoalbuminaemia (p=0.014) were predictive of Crohn's disease on CE. Management was altered in 62% (n=164) of patients. Thirteen percent underwent therapy change (n=21; azathioprine/ methotrexate (n=6), steroids (n=7), infliximab (n=2) or mesalazine (n=6)). 49% (n=81) were discharged after a normal CE and 3% (n=5) were treated for irritable bowel syndrome. 42 patients (26%) had repeat histology post CE, 5 patients had their NSAIDs stopped and ten patients underwent other investigations/radiology post CE. An eventual diagnosis of Crohn's disease was made in 12% (n=31) after a mean follow up of 15 months (range 1–84). 14 patients had repeat histology of which 4 were confirmed Crohn's disease on biopsy and the other 10 were non-specific changes but with evidence of macroscopic ulceration and/or stricturing on enteroscopy. A further 14 patients were confirmed on the basis of their CE findings and their clinical response to treatment. In 3 patients management was unchanged either because of symptom resolution or treatment initiation prior to CE. Conclusion: CE is a useful tool in patients with suspected Crohn's disease with a positive impact on patient management. Abdominal pain, diarrhoea and hypoalbuminaemia appear to be highly predictive of a yield with CE. CE also helps to rationalise management in those with normal findings.